Anisotropic alumina ceramics with isotropic optical properties - Akio IKESUE; Yan Lin AUNG (Journal of Advanced Ceramics, 2023)
Excellent mechanical and isotropic optical properties are achieved simultaneously from fully dense polycrystalline advanced alumina ceramics with a hexagonal crystal structure, which are optically anisotropic. A small amount (240 ppm) of ZrO2 additive is used to synthesize the transparent alumina ceramics with an average grain size of 0.7 µm, and locally detected optical distortion (birefringence) is extremely minimized, less than 20 nm/pass. Total transmittance (86%) of the alumina ceramics (thickness = 0.3 mm) in ultraviolet (UV) to infrared (IR) regions is similar to that of commercial c-axis sapphire single crystals produced by Czochralski (CZ) method, while the extinction ratio in the visible wavelength area is over 25 dB. Like glass and the c-axis sapphire single crystals, the alumina ceramics can clearly display texts and images on liquid crystal display (LCD) screens. A grain boundary phase of nano-sized Al2O3–ZrO2 composition (amorphous) is formed at the grain boundary of the advanced alumina ceramics, which enhances four-point bending strength and fracture toughness (KIC) simultaneously to 921 MPa and 6.8 MPa·m0.5, respectively, and hence the mechanical properties are superior to those of the sapphire single crystals.